2018
DOI: 10.54386/jam.v20i1.506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weather parameters on incidence of insect pests of cucumber in eastern Bihar

Abstract: The insect-pests infestation in cucumber leads to severe injury to its’ vegetative parts and fruits by epilachna beetle, red pumpkin beetle, whitefly, pumpkin caterpillar, leaf minerand fruit fly. The present investigation was taken upduring 2014 and 2015 to study the population dynamics of prevailing six insect-pests of cucumber and its natural enemies inrelation to weather parameters.The correlation studies between insect pests and weather parameters revealed that the melon fruit fly (Bactrocera cucurbitae C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Rainfall had a positive and non significant correlation with the population of ladybird. Corroborating with the results of present studies Saha et al [10] reported that coccinella in cucumbers was positively correlated with temperature and negatively correlated with humidity. Dhurva and Soni [6] in rice ecosystem reported that maximum temperature, minimum temperature, rainfall and sunshine hours showed negative non significant relationship with the population of ladybird.…”
Section: Weather Parameters Impact On Incidence Of Coccinelid Beetlesupporting
confidence: 92%
“…Rainfall had a positive and non significant correlation with the population of ladybird. Corroborating with the results of present studies Saha et al [10] reported that coccinella in cucumbers was positively correlated with temperature and negatively correlated with humidity. Dhurva and Soni [6] in rice ecosystem reported that maximum temperature, minimum temperature, rainfall and sunshine hours showed negative non significant relationship with the population of ladybird.…”
Section: Weather Parameters Impact On Incidence Of Coccinelid Beetlesupporting
confidence: 92%
“…An effective approach of pest control that incorporates knowledge about peak period of pest occurrence along with chemical application can aid in control of the pest. According to Kaur et al, (2021) and Saha et al, (2018) pest occurrence, growth and activity are primarily caused by ambient weather, either directly or indirectly, along with the crop. A significant relationship has been found between these parameters and the pest's seasonal incidence.…”
mentioning
confidence: 99%